MODIFICATION OF BAYAH BANTEN NATURAL ZEOLITE AS HETEROGENEOUS CATALYST IN BIODIESEL PRODUCTION - Hartono, Rudi -; Wijanarko, Anondho -; Hermansyah, Heri - (Journal of Applied Engineering Science, 2019)
Natural zeolite bayah banten  (ZABBrht) as a heterogeneous catalyst for ion exchange  is impregnated using KOH in 100 ml of aquadest. This catalyst is reacted with methanol and   cooking  oil to produce biodiesel. It was Performed at various temperature and time to get the optimum condition for making biodiesel. This heterogeneous catalyst is environmentally friendly and easily separated and can be reused. The molar ratio of used cooking oil and methanol (1:7) was used is transesterification. The yield of biodiesel at various optimum temperatures and times is 94% (50 gram of KOH/100mL), 87,8%  75 gram of KOH/100mL), 86% (100 gram of KOH/100mL). Biodiesel results were analyzed by GC Ester content and modified catalysts were characterized using XRD, FTIR, SEM-EDX